Improvement Prioritization in Bike Lane Attributes Based on the View of Different Gender and Age Cyclist Groups (Case Study: Qazvin City, Iran) - Zarabadipour, Shima; Ramezani-Khansari, Ehsan; Abdolrazaghi, Alireza (Communications - Scientific Letters of the University of Zilina, 2023)
A survey of cyclists in the city of Qazvin, Iran, was conducted by focusing on improving the bike lane attributes (increasing width, increasing attractiveness or appeal of the bike lane (painting, planting …), improving pavement conditions, improving sight distance and removing obstacles in the bike lane). It was seen that there was no difference between age groups. Two important priorities for the men group were increasing the lane width and improving the sight distance, while the women considered improving the pavement conditions and the appeal of the bike lanes. Increasing the lane width and improving the pavement conditions for the recreational group and increasing the lane width and improving the sight distance for the non-recreational group were the most important improvements. It can be said that increasing the width of the bike lane was the most important factor for almost all groups.
Keywords: bike lane; gender; age; cycling purpose; transportation infrastructure